Cancer in English prisons: a mixed-methods study of diagnosis, treatment, care costs and patient and staff experiences - Elizabeth A Davies; Margreet Lüchtenborg; Rachael Maree Hunter; Renske Visser; Jennie Huynh; Ross Pow; Emma Plugge; Rachel M Taylor; Jo Armes (Health and Social Care Delivery Research)
Background The increasing size of the ageing English prison population means that non-communicable diseases such as cancer are being more commonly diagnosed in this setting. Little research has so far considered the incidence of cancer in the English prison population, the treatment patients receive when they are diagnosed in a prison setting, their care costs and outcomes or their experiences of care compared with those of people diagnosed in the general population. This is the first mixed-methods study that has been designed to investigate these issues in order to inform recommendations for cancer practice, policy and research in English prisons. Methods We compared cancer diagnoses made in prison between 1998 and 2017 with those made in the general population using a cohort comparison. We then used a cohort comparison approach to patients’ treatment, survival, care experiences and costs of care between 2012 and 2017. We also conducted qualitative interviews with 24 patients diagnosed or treated in prison, and 6 custodial staff, 16 prison health professionals and 9 cancer professionals. Findings were presented to senior prison and cancer stakeholders at a Policy Lab event to agree priority recommendations. Results By 2017 cancer incidence in prison had increased from lower levels than in the general population to similar levels. Men in prison developed similar cancers to men outside, while women in prison were more likely than women outside to be diagnosed with preinvasive cervical cancer. In the comparative cohort study patients diagnosed in prison were less likely to undergo curative treatment, particularly surgery, and had a small but significantly increased risk of death. They also had fewer but slightly longer emergency hospital admissions, lower outpatient costs and fewer planned inpatient stays. While secondary care costs were lower for patients in prison, when security escorts costs were added, emergency care and total costs were higher. Control and choice, communication, and care and custody emerged as key issues from the qualitative interviews. People in prison followed a similar diagnostic pathway to those in the general population but experienced barriers arising from lower health literacy, a complex process for booking general practitioner appointments, communication issues between prison staff, surgical, radiotherapy and oncology clinicians and a lack of involvement of their family and friends in their care. These issues were reflected in patient experience survey results routinely collected as part of the annual National Cancer Patient Experience Survey. The four priorities developed and agreed at the Policy Lab event were giving clinical teams a better understanding of the prison system, co-ordinating and promoting national cancer screening programmes, developing ‘health champions’ in prison and raising health literacy and awareness of cancer symptoms among people in prison. Limitations We could not identify patients who had been diagnosed with cancer before entering prison. Conclusion Healthcare practices and policies both within prisons and between prisons and NHS hospitals need to be improved in a range of ways if the cancer care received by people in prison is to match that received by the general population. Future work Evaluating new policy priorities. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: 16/52/53) and is published in full in Health and Social Care Delivery Research; Vol. 13, No. 3. See the NIHR Funding and Awards website for further award information. Plain language summary Background Information on the diagnosis of cancer and experience of cancer care in prison is sparse both in the United Kingdom and globally. This is the first national study to investigate this topic with the aim of informing English prison cancer practice, policy and research. Methods We analysed English cancer data for the years 1998–2017 and previously collected National Cancer Patient Experience Survey data. We also interviewed 24 patients receiving cancer care in prison, and 32 prison and health professionals. Findings were analysed and presented at a half-day ‘Policy Lab’ attended by people with lived experience of being in prison, and professionals working to develop health services in prisons and National Health Service cancer care services. The aim was to develop and agree priority recommendations for healthcare practice and policy for patients with cancer in English prisons. Results Cancer diagnoses in the prison population were initially lower in 1998 but increased to levels comparable to those in the general population by 2017. Men in prison were diagnosed with similar cancers to those outside, while women in prison were more commonly diagnosed with precancerous cervical changes. Patients in prison were less likely to undergo treatment to cure their cancer, particularly surgery to remove the tumour, and had a small but significantly increased risk of death, half of which was explained by treatment differences. People in prison had fewer but slightly longer emergency hospital admissions than the general population, and the cost of National Health Service hospital care was lower in the first 6 months due to fewer outpatient attendances and planned inpatient stays. However, once emergency care and security escort costs were added, the overall hospital care costs for people in prison were higher. Three core themes were identified from the interviews: control and choice, communication, and care and custody. People in prison followed similar diagnostic pathways to those outside but experienced barriers including lower health literacy (the ability to obtain and understand information about health and the services needed to make health decisions), a complex process for booking general practitioner appointments, and communication issues both between prison staff and with National Health Service clinicians involved in cancer care. These findings were largely confirmed by a separate analysis of National Cancer Patient Experience Survey data. At the Policy Lab event, the lived experience and policy and practitioner stakeholders gave priority to providing clinical teams with a better understanding of the prison system, co-ordinating and promoting national cancer screening programmes within prisons to increase uptake, developing the role of ‘health champions’ and raising health literacy and awareness of cancer symptoms among people in prison. Conclusions Healthcare practices and policies both within prisons and between prisons and National Health Service hospitals need to be improved in a range of ways if the cancer care received by people in prison is to match that received by the general population. Scientific summary Background The growing and ageing English prison population makes it increasingly important that prison and health professionals, policy-makers and advocacy groups have much more accurate and detailed data on cancer incidence, treatment, outcomes, care costs, and patients’ experiences of diagnosis and treatment for this population group. Cancer is common in the general population, but currently there is very little research either in the UK or internationally that has considered how cancers are diagnosed in prison, how patients in prison are treated or cared for, how the experiences of people diagnosed in prison differ from those of people in the general population or how care costs may differ. This mixed-methods study is, to our knowledge, the first to investigate these factors using national cancer data and in-depth interviews to identify barriers to and enablers of accessing cancer services. The overall aim is to develop recommendations that can inform improved cancer practice, policies and research between NHS services and English prisons. Methods We used previously unanalysed National Disease Registration Service (NDRS) data to identify invasive cancers and cervical cancers in situ diagnosed in prison and the general population based on residential postcode at diagnosis from 1998 to 2017. Population data from the Ministry of Justice and the Office for National Statistics were used to calculate age-standardised incidence rates and incidence rate ratios in each population cohort. We then used a comparative cohort approach, matching patients diagnosed with a first primary cancer in prison during 2012–7 to the general population using a 1 : 5 ratio based on 5-year age group, gender, diagnosis year, cancer site and disease stage. These cancer registration records were then linked to Hospital Episode Statistics (HES) and radiotherapy treatment and systemic anti-cancer therapy data sets to obtain information on hospital admissions, length of stay, and curative treatment. We used logistic regression and Cox proportional hazards modelling to compare access to curative treatment and survival for these patients, and adjusted for matching variables, ethnicity and comorbidity. To analyse and compare the costs of treatment, we used a cohort of patients from 2012 to 2017, 6 months from diagnosis. Outpatient and inpatient HES data were costed using NHS Reference Costs and inflated to 2017–8 costs. We also conducted 55 semistructured, qualitative, audio-recorded interviews with people with cancer in prison (n = 24), custodial staff (n = 6), prison healthcare staff (n = 16) and oncology specialists (n = 9). Patients were identified and approached by prison healthcare services. Experts by Experience – people with previous experience of having cancer in prison or of caring for another patient in prison – were involved in designing, conducting and analysing the interviews. Professional participants were recruited via mailing lists, newsletters and social media. Interviews were conducted either face to face or over the telephone. Data were transcribed and analysed using reflexive thematic analysis. We also compared recent National Cancer Patient Experience Survey (NCPES) data available from patients diagnosed in prison with those from patients in the general population for the years 2012–8. Key findings were presented to a senior group of prison and health professionals, cancer policy stakeholders and Experts by Experience at a facilitated half-day Policy Lab event. The aim of the event was to determine what this group collectively considered the main feasible and immediate priorities for improving cancer care policies for patients in prison. Results We identified 2015 incident cancers among 1556 men and 459 women in prison between 1998 and 2017. The age-standardised incidence rate for men in prison was initially lower than that for the general population but increased to similar levels by 2017. Women in prison were far more likely to be diagnosed with cervical cancer in situ than those in the general population [incidence rate ratio 2.13, 95% confidence interval (CI) 1.91 to 2.36]. Between 2012 and 2017 a lower percentage of patients in prison had hospital admissions than general population controls (40% vs. 46%). Patients from prisons had slightly longer hospital emergency admissions than controls (median 6 vs. 5 days; p = 0.003). Patients diagnosed in prison were far less likely to undergo curative treatment [odds ratio (OR) 0.63, 95% CI 0.53 to 0.75] than the general population. The difference was most pronounced for surgical resections (OR 0.64, 95% CI 0.53 to 0.78). Being diagnosed with cancer in prison carries a small but significantly increased risk of death [hazard ratio (HR) 1.16, 95% CI 1.03 to 1.30]. Differences in treatment with curative intent explain half of this increased risk (HR 1.08, 95% CI 0.96 to 1.22): 879 prison and 4326 general population cancer diagnoses were identified in HES. The adjusted 6-month cost of cancer care was significantly lower for people in prison (−£1216, 95% CI −£1638 to −£795), driven by fewer outpatient attendances and planned inpatient stays and hence a significantly lower cost for planned care. People diagnosed in prison had higher emergency care costs than their matched general population controls (£497, 95% CI £375 to £619) and higher total costs when security escort costs were added. From the qualitative interview data, we identified three core themes: communication, care and custody, and control and choice. By mapping our findings to the cancer care pathway, we identified that people in prison follow a similar diagnostic pathway to people in the general population. However, there are several additional barriers to being diagnosed with cancer in prison, including health literacy, the complex process for booking a general practitioner appointment, and communication both between prison staff and with oncology clinicians. Not all barriers were specific to prison, with some (i.e. late diagnosis) experienced by people residing in the general population, but many are exacerbated by the prison environment. These findings were largely confirmed in a separate analysis of previously collected NCPES data, which showed patients in prison reporting worse experiences of cancer care than those in the general population. The Policy Lab event identified many potential ways of improving cancer care, with priority being given to providing clinical teams in the NHS with a better understanding of the prison system, promoting cancer screening programmes in prisons to increase uptake, developing the role of ‘health champions’ in prison and raising health literacy and awareness of cancer symptoms in prison. Conclusions Cancer incidence in English prisons rose between 1998 and 2017, with patients diagnosed in prison having fewer but longer emergency hospital admissions, fewer curative treatments, and a lower survival rate. Following a cancer diagnosis, people in prison have significantly lower planned care costs but higher emergency care costs, and an overall higher care cost due to the additional provision of security escorts. This is alongside evidence of poorer self-reported experiences of care in both qualitative interviews and NCPES data. Cancer care in prison is complex, not least because people in prison move between a health and a prison environment. However, tensions between control and choice in prison healthcare impacted on patients’ experience of cancer care in terms of symptom management, accessing information about their illnesses, and the involvement of family in their care. Initial policy priorities are to improve understanding between prison and cancer clinical teams to improve care, and to develop the role of ‘health champions’ in prison to raise health literacy and awareness of national cancer screening and potential cancer symptoms among people in prison. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: 16/52/53) and is published in full in Health and Social Care Delivery Research; Vol. 13, No. 3. See the NIHR Funding and Awards website for further award information.